Conclusions - Minyoung Kwon (A+BE: Architecture and the Built Environment)
This research has explored the relationship between user satisfaction and design factors for office renovations considering energy efficiency. The findings of this research strongly support user-focused renovations of office buildings. My motivation for this research started from the consideration of comfort and satisfaction of building users and the focus on providing better and comfortable work environments for office users. The focus on user comfort and satisfaction is important, because literature shows that the increase of user satisfaction leads to the improvement of productivity and less absenteeism in workspaces.